Viscosities (η) of Polyvinyl Pyrrolidone in its Aqueous Solutions at 292.9 K - Singh, Man; Teotia, Sunita; Ram, Babu (Asian Journal of Chemistry, 2010)
The increasing magnitude of relative viscosity (ηr), specific viscosity(ηsp) and reduced viscosity (ηred) values of aqueous polyvinylpyrrolidone (PVP) solutions with its concentration was marked tobe directly correlated with its structural interactions with watermolecules and hydrogen bonded water structure seems to be enhancedin presence of PVP molecules. The concentration effect wasstudied and the observations were seen to enhance the structuremaking effect of PVP on water. The hydrophilic and hydrophobicinteractions between PVP and water molecules were seen to begoing on and the torsional forces of PVP molecules and hydrogenbonded PVP in aqueous solution were seen to absorb some of theheat content from the solution itself.